2021
DOI: 10.20452/pamw.16119
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to severe Vitamin D deficiency increases the risk for COVID-19 mortality in patients treated in a respiratory intensive care unit

Abstract: The association between vitamin D insufficiency and increased risk of respiratory tract infection has been widely discussed before the COVID-19 pandemic [1][2][3]. Interestingly, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The presence of additional conditions was a factor associated with higher chances of being admitted to ICUs ( 6 , 7 , 10–13 , 15 , 17–19 , 23 , 28 , 33 ). On the pressing issue of killer pandemics, researchers of the current research agree with previous studies, which indicated that further detailed analysis, stronger evidence with larger sample sizes, and valid research techniques are crucial to increase generalizability ( 10 , 13 , 15 , 21 , 23–25 ). A meaningful aspect of the study is also the fact that subjects included in the study had not been previously vaccinated for COVID-19.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The presence of additional conditions was a factor associated with higher chances of being admitted to ICUs ( 6 , 7 , 10–13 , 15 , 17–19 , 23 , 28 , 33 ). On the pressing issue of killer pandemics, researchers of the current research agree with previous studies, which indicated that further detailed analysis, stronger evidence with larger sample sizes, and valid research techniques are crucial to increase generalizability ( 10 , 13 , 15 , 21 , 23–25 ). A meaningful aspect of the study is also the fact that subjects included in the study had not been previously vaccinated for COVID-19.…”
Section: Discussionsupporting
confidence: 85%
“…A total of 83 confirmed COVID-19 cases were enrolled in a retrospective, observational, single-center respiratory-ICU study in Italy. The study demonstrated that moderate–severe Vitamin D hypoVitaminosis may predict worse prognosis and increased in-hospital mortality in patients with severe COVID-19 and acute respiratory failure ( 13 ). Decreased serum levels of Vitamin D versus the healthy participants was exhibited in a study with 100 participants, consisting of 50 healthy and 50 ICU-admitted COVID-19 ( p = 0.0024).…”
Section: Background and Aimsmentioning
confidence: 99%
See 2 more Smart Citations